الوحدة النفسية وعلاقتها بتقدير الذات لدى طلبة كلية التربية جامعة مصراتة (Faculty of Education Scientific Journal, 2024)
This research is entitled “Psychological Loneliness and its Relationship to Self-esteem among Students of the College of Education, Misurata University. The current research aims to find out the relationship between psychological loneliness and self-esteem among students of the College of Education, Misurata University. The research problem is defined as the following question:Is there a relationship between psychological loneliness and self-esteem among students of the College of Education at Misurata University?Some other questions branch out from this question, which are evident in the following questions:What is the level of psychological loneliness among students of the College of Education at Misurata University?What is the level of self-esteem among students of the College of Education at MU?Are there statistically significant differences in the level of psychological loneliness due to the gender variable? (Males/ Females)?   The descriptive, correlational approach was relied upon, and the population represented 2012 male and female students. The research sample was randomly selected, amounting to (201) male and female students, using the psychological loneliness scale, which was originally prepared by Russell and Catrona and modified by Qashqoush (2012-2013). The researchers also relied on the scale Self-esteem, which was first designed by the American researcher Cooper Smith in the year (1967), and was also modified and translated by Qashqoush (2012-2013), as a research tool, to find the studied apparent relationship, where the researchers used the statistical program (SPSS) to analyze the data, and the research reached The following results:-The level of psychological loneliness among students of the College of Education/ Misurata University was low.The level of sense of self-esteem among students of the College of Education/ Misurata University was high.There is a very strong negative relationship with a significant significance between the level of psychological loneliness and self-esteem among students of the College of Education/ Misurata University.Furthermore, it recommends activating the role of the psychologist within universities by providing them with psychologists and counselors to interact with students’ problems. Researchers also suggest that there should be studies based on studying the relationship between psychological loneliness and the level of ambition.
Keywords: Psychological loneliness; Self-esteem; university student